Implementasi Sistem dan Prosedur Penerimaan Pajak Pertambahan Nilai pada Kantor Pelayanan Pajak Pratama Makassar Utara - Hajering Hajering (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this study is to determine the implementation of the system and procedures for receiving value added tax at the Value Added Tax service office at the North Makassar Pratama Tax Service Office. This study uses a descriptive qualitative method, where documents are obtained in several studies of various literature that are related to the problems discussed in this study to strengthen the basic concept of theory and problem solving in the research on the implementation of the system and procedures for receiving value added tax at the North Makassar Pratama Tax Service Office. The results of this study illustrate the implementation of value added tax using a flowchart. The system and procedures for receiving Value Added Tax at the North Makassar Pratama Tax Service Office are very simple, where the system and procedures already use a computer system. However, taxable entrepreneurs still follow the requirements that have been determined in terms of the completeness of the required files. The implementation of the system and procedures for receiving Value Added Tax at the North Makassar Pratama Tax Service Office has been implemented based on Law Number 42 of 2009. The implementation of the system and procedures for receiving Value Added Tax at the North Makassar Pratama Tax Service Office is still less effective and efficient. The system and procedure for receiving Value Added Tax at the Pratama Tax Service Office is very simple, where the system and procedure already use a computer system. However, taxable entrepreneurs still follow the requirements that have been determined in terms of the completeness of the required files. The implementation of the system and procedure for receiving Value Added Tax at the Pratama Tax Service Office of North Makassar has been implemented based on Law Number 42 of 2009. The implementation of the system and procedure for receiving Value Added Tax at the Pratama Tax Service Office of North Makassar is still less effective and efficient.